A KIAI MUHAMMAD KIRAMU (ISTAD) AND SERAT MENAK: THE JOURNEY OF ISLAMIC PREACHING IN KEDUNGPOG, NGLIPAR, GUNUNGKIDUL, YOGYKARTA (1885 – 1900 AD) - Wahyu Hadi Maulana Wahyu (UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
Islamic preaching in Indonesia during the colonial era was not limited to oral preaching, but also through writing. For Indonesian scholars, literary works have a very important role in the spread of Islam in Indonesia, among the literary works used by Islamic preachers in Indonesia is through the literary work of Serat Menak by Kiai Kiramu in the Kedongpoh area, Nglipar, Gunung Kidul, Yogyakarta. Serat Menak by Kiai Kiramu which broadly contains the journey of the struggle of Dewi Adaninggar Kelaswara who pursues the love of Wong Agung Jayengrono (Amir Hamzah: Uncle of the Prophet Muhammad saw.) as a medium of preaching and motivation to his students. Serat Menak written by Kiai Kiramu was written on sheets of paper which were then read to his students as entertainment and motivation as a reference for social behavior. The implication of reading this Serat Menak is the emergence of encouragement and prohibition of pursuing lust for students and the surrounding community as a guide for living in society. This research uses a philological approach with codicology and textology theories, exploring the intricacies of the manuscript, from its physical aspects to its textual structure, as well as its understanding. This research is interesting as a description of the dynamics of Islamic preaching by Indonesian scholars through literary works and as a reflection of social behavior.